2011
DOI: 10.3390/polym3041684
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Cell-Seeded Nanofiber Scaffolds for Neural Repair

Abstract: Central and peripheral neural injuries are traumatic and can lead to loss of motor and sensory function, chronic pain, and permanent disability. Strategies that bridge the site of injury and allow axonal regeneration promise to have a large impact on restoring quality of life for these patients. Engineered materials can be used to guide axonal growth. Specifically, nanofiber structures can mimic the natural extracellular matrix, and aligned nanofibers have been shown to direct neurite outgrowth and support axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 292 publications
0
45
0
Order By: Relevance
“…For example, cellulose acetate is actively used for bone and cartilage tissue engineering because of its biocompatibility and mechanical strength (Katoh and Urist 1993;Mayer-Wagner et al 2011). In addition, CA has been investigated as a material for vascular tissue and peripheral nervous system recovery (Han and Cheung 2011;Pooyan et al 2012). However, few studies have employed 3D cultures of astrocytes on CA nanofiber.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cellulose acetate is actively used for bone and cartilage tissue engineering because of its biocompatibility and mechanical strength (Katoh and Urist 1993;Mayer-Wagner et al 2011). In addition, CA has been investigated as a material for vascular tissue and peripheral nervous system recovery (Han and Cheung 2011;Pooyan et al 2012). However, few studies have employed 3D cultures of astrocytes on CA nanofiber.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amount, length, fusion index, and maturation index of myotubes on the aligned‐PCL/PANI nanofibers were further enhanced, especially myotube numbers increased ∼80% compared with R‐PCL scaffolds. These results indicated that PANI could provide two different types of guidance cues, including topographical and electrical cues, to promote effectively myoblast formation, and well‐aligned fibers can provide better topographical cues for cell growth compared with random fibers . The poly( l ‐lactide‐ co ‐epsilon‐caprolactone) (PLCL)/conductive PANI nanofibers exhibited similar functions, the electrically conductive properties and formation of myotubes on the PLCL/PANI nanofibers were distinctly enhanced (Fig.…”
Section: Cnms Used In Tissue Engineeringmentioning
confidence: 83%
“…However, it is important to note that the degradation rate of polymers is different between the bulk material and the nanofibre-based scaffolds. For some polymers, the degradation rate of larger structures is faster than that of nanofibres due to autocatalysis in larger structures [66]. Nevertheless, the hydrolytic degradation was found to be much more rapid for nanofibrous scaffolds obtained by TIPS in comparison to solid-walled scaffolds, even if the wettability in the nanofibrous scaffold is smaller because of small interfibre spacing and the large amount of relatively-hydrophobic surface area.…”
Section: Propertiesmentioning
confidence: 99%